Robert and the great Pepperoni - Seuling, Barbara (Cricket Books, 2001)
Second-grader Robert, who desperately wants a dog of his own, starts a pet sitting business, but when he finds a stray dog, the best he can do is to keep him temporarily and train him so he can be adopted by someone else.